Modified Risk of Malignancy Index (RMI 5) in ovarian tumor - Joshi, Rijuta; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To evaluate the role of modified RMI (RMI 5) in pre-operative evaluation of ovarian tumor. Methods: It was a prospective cross sectional study done in Paropakar Maternity and Women’s Hospital from May to August 2018. During the study, 72 women with ovarian tumor were analyzed. RMI5 was calculated using the ultrasound score, Doppler score, menopausal status and CA125. Cut-off of 200 was used for malignancy discrimination. Chi square test was used to calculate the statistical significance which was set at 0.05. Receiver Operator Characteristics curves for RMI and its individual parameters were plotted using SPSS. Results: There were 72 ovarian tumors operated in four months and mean age was36 years with 10 (14%) at post-menopause. The mean value of RMI 5 was 38 for benign tumors, 80 for borderline tumors and 899 for malignant tumors. The area under curve for RMI 5 was 0.993 for cut-off of 200. The diagnostic accuracy of RMI 5 was 94.4 which was similar to that of Doppler score 2 (94.7) while it was much higher than that of the rest of the parameters (CA-125: 72, ultrasound score: 87 and postmenopausal status: 88.9). Conclusions: RMI 5 is better for malignancy prediction of ovarian masses instead of individual parameters like menopausal status, CA125 and ultrasound score.